2020
DOI: 10.1039/d0cb00075b
|View full text |Cite
|
Sign up to set email alerts
|

Long-range PEG stapling: macrocyclization for increased protein conformational stability and resistance to proteolysis

Abstract: Long-range stapling of two Asn-linked PEG oligomers via olefin metathesis substantially increases the conformational stability of the WW and SH3 domain tertiary structures and the GCN4 coiled-coil quaternary structure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 93 publications
1
11
0
Order By: Relevance
“…[27][28][29][30][31][32][33] We recently showed that stapling via olefin metathesis vs. the copper-catalyzed azide-alkyne cycloaddition (CuAAC) provide similar increases in the conformational stability of WW, a βsheet miniprotein derived from the WW domain of the human protein Pin1. 34,35 We observed similar levels of stabilization for staples comprised of discrete polyethylene glycol oligomers (i.e., PEG staples) vs. conventional hydrocarbon staples. The most important determinant of PEG-staple-based stabilization in WW is that the two crosslinked groups be far apart in primary sequence but close together in the folded tertiary structure.…”
Section: Introductionmentioning
confidence: 64%
See 2 more Smart Citations
“…[27][28][29][30][31][32][33] We recently showed that stapling via olefin metathesis vs. the copper-catalyzed azide-alkyne cycloaddition (CuAAC) provide similar increases in the conformational stability of WW, a βsheet miniprotein derived from the WW domain of the human protein Pin1. 34,35 We observed similar levels of stabilization for staples comprised of discrete polyethylene glycol oligomers (i.e., PEG staples) vs. conventional hydrocarbon staples. The most important determinant of PEG-staple-based stabilization in WW is that the two crosslinked groups be far apart in primary sequence but close together in the folded tertiary structure.…”
Section: Introductionmentioning
confidence: 64%
“…27–33 We recently showed that stapling via olefin metathesis vs. the copper-catalyzed azide–alkyne cycloaddition (CuAAC) provide similar increases in the conformational stability of WW, a β-sheet miniprotein derived from the WW domain of the human protein Pin1. 34,35 We observed similar levels of stabilization for staples comprised of discrete polyethylene glycol oligomers ( i.e. , PEG staples) vs. conventional hydrocarbon staples.…”
Section: Introductionmentioning
confidence: 67%
See 1 more Smart Citation
“…In particular, INCYPRO provides straight‐forward access to diverse linker structures. [81] In general, it can be expected that more cyclization strategies will be developed which allow the simultaneous introduction of an additional functionality (e. g. PEG chains [84] or photo‐switchable moieties[ 85 , 86 ]).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, steric hindrance by these size-increasing moieties also protects against proteolytic degradation. [13][14][15] ; Class 2: increase in size via controlled oligomerization; 16 Class 3: covalent linking to long-living serum protein (e.g., FDA-approved drugs albiglutide and dulaglutide, exanatide that conjugated to albumin and the IfG4 Fc domain) [17][18][19] and Class 4: incorporation of moieties that bind non-covalently to serum proteins such as albumin, [20][21][22][23] immunoglobulin, 24,25 FcRn, 26 transthyretin, 27 and transferrin. 28,29 An important example in the last class is lipidation of peptides to allow interaction with serum albumin.…”
Section: Introductionmentioning
confidence: 99%